Flame retardancy of phosphorus-containing ionic liquid based epoxy networks. (December 2016) - Sonnier, Rodolphe; Dumazert, Loïc; Livi, Sébastien; Nguyen, Thi Khanh Ly; Duchet-Rumeau, Jannick; Vahabi, Henri; Laheurte, Pascal
Abstract: Various amounts of a phosphonium ionic liquid (IL169) were used as curing agents as well as flame retardants of epoxy prepolymer in order to prepare epoxy networks with improved fire properties. The flame retardancy of these resins was investigated using thermogravimetric analysis (TGA), pyrolysis-combustion flow calorimetry (PCFC) and cone calorimetry. Phosphonium ionic liquid significantly reduced flammability without further addition of flame retardants due to the high amount of phosphorus (up to 3.69 wt%). The Peak of heat release rate decreases from 1099 kW/m 2 to 300 kW/m 2 in cone calorimeter at 35 kW/m 2 when incorporating 30 phr of IL169. Phosphorus modifies pyrolysis pathway, promotes charring and may act as flame inhibitor. The char layer protects the underlying polymer, leading to a high unburnt polymeric fraction. Char properties were studied using PCFC, Raman spectroscopy and X-ray tomography. Phosphorus improved the graphitization of the char and its thermo-oxidative stability.